Nominee Arrangement in the Practice of Land Sale and Purchase in Indonesia - KRESNADJAJA, Indrasari; DHARSANA, I Made Pria (Protection: Journal Of Land And Environmental Law, 2024)
The practice of nominee agreements has occurred in Indonesia repeatedly; the agreement uses the power of attorney where the agreement uses the name of an Indonesian citizen to transfer power of attorney to a foreign citizen. A Nominee Agreement made by two parties, namely between an Indonesian citizen and a foreign citizen as the attorney (Nominee), is made through an agreement package to provide all authority that may arise in the legal relationship between a person and his land to a foreign party as a person who is given the power to act as the actual owner. The agreement borrows the name of an Indonesian citizen as the Nominee, and this is a legal smuggling because its substance is contrary to Article 21 paragraph (1) and Article 26 paragraph (2) of Law Number 5 of 1960 concerning the UUPA. In addition, the existence of a loan agreement in the name must be based on the terms and principles of freedom of contract as stipulated in Article 1320 and Article 1338 Paragraph (1) of the Civil Code. For this reason, an objective and comprehensive attitude and understanding are needed from the NotaryNotary in assessing the contents of the land sale and purchase agreement, primarily related to the one-sided agreement. In reality, in the author's opinion, nominee agreements do not comply with the positive law in force in Indonesia because the purpose of this agreement contains elements of bad ethics.